Optimizing Agribusiness Supply Chain Management in Increasing Agricultural Yields - Tri Waluyo (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2023)
Effective supply chain management can contribute significantly to operational efficiency and increased agricultural productivity. This research will explore key aspects of the agricultural supply chain, including production, distribution, storage and marketing of agricultural products. This research uses a qualitative approach with descriptive methods. The research results show that optimizing agribusiness supply chain management with a sustainable approach can significantly increase agricultural yields. The application of information technology and strong partnerships between stakeholders in the supply chain results in increased efficiency and responsiveness to market fluctuations. Identifying and managing risks with careful planning has also proven effective in maintaining supply chain resilience to external changes. In addition, diversification of suppliers and markets contributes to flexibility and balance, reducing risks associated with market fluctuations. In the context of sustainable agriculture, practices such as environmentally friendly farming methods, sustainable management of natural resources, and environmental impact monitoring are proven to improve agricultural quality and productivity in the long term. The results of this research provide an in-depth understanding of how the integration of effective supply chain management with a sustainable approach can create optimal conditions for the growth and sustainability of the agricultural sector.